Resource allocation for wireless information and power transfer based on WBAN - Gu, Haijun; Li, Zhijun; Wang, Liheng; Ling, Zhuang (Physical communication, 2019)
In this paper, a simultaneous wireless information and power transfer (SWIPT) system with a relay in wireless body area network (WBAN) is studied, where the relay harvests energy from the radio frequency (RF) signals sent by the access point (AP), then uses RF energy to transmit energy to the user and forward the information to the AP, respectively. Firstly, we propose a planar transmission model based on the time switching (TS) and power splitting (PS) protocols. The sensor nodes are placed on the human torso in this model. In order to explore the system performance, the optimal information throughput for the two protocols is given subject to the energy harvesting and consumption balance. Then, corresponding optimal power splitting and time switching ratios which maximize the information throughputs are obtained. Besides, the effects of the relay position on system performance are also discussed. Finally, while considering the relay transmission power constraint, we solve the dynamic power allocation problem by the Lagrange multiplier iteration method. Numerical results and analysis show that our proposed optimal strategy achieves the optimal throughput. Moreover, the TS protocol has better performance than the PS protocol in dynamic model.